Analytic Hierarchy Process (AHP) and Fuzzy Analytic Hierarchy Process (FAHP) with Vikor method for evaluation of student performance / Ahmad Hisyamuddin Abd Rahman - Abd Rahman, Ahmad Hisyamuddin (2020)
Education is the key to success in life and it allows individuals and society to progress socially and economically. The quality of education is assessed through the way students live and process of their learning in the university. There are two important processes to make sure the quality of students learning which are their academic and the involvement in university. Therefore, the Analytic Hierarchy Process, Fuzzy Analytic Hierarchy Process and VIKOR method, a decision-making instrument was constructed in this project that focuses on the selection process to calculate and to rank the most successful student in the university. In this research, three important main criteria and several sub-criteria have been considered, the main criteria which are academic, club involvement and participation. The weighting of each criterion and sub-criteria were calculated by using the Analytic Hierarchy Process (AHP) and Fuzzy Analytic Hierarchy Process (FAHP) method. The results will be rank by using Vise Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR method).